Undergraduate vs Master Students: Who is more anxious on final exams? - Hidayat, Novita Rahmawati; Pratama, Muhammad Fikri; Chusairi, Achmad (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Students are an essential factor in society as an educated group, yet they cannot escape the issue of anxiety. Anxiety is an unpleasant feeling that can manifest in physiological, emotional, and cognitive symptoms, which can hinder one's best performance. The aim of this research is to determine the differences in anxiety levels between undergraduate and master's students approaching the final semester examinations. The research participants included 35 undergraduate and master's students selected through non-probability purposive and quota sampling methods. The anxiety instrument employed was the anxiety scale levels in facing final semester examination. Independent t-test analysis was employed. The results of this study showed p score > 0.05, meaning that there was no significant difference in anxiety levels between undergraduate and master's students during the Final Semester Examination. The implication shows that anxiety level does not depend on the educational level. Further research may consider other factors to gain more comprehensive understanding and contribute the level of student anxiety in undergraduate and master student also consider what interventions that can help reduce anxiety of postgraduate and master students during the final examination period.Mahasiswa merupakan faktor penting dalam masyarakat sebagai kelompok terdidik ternyata tak dapat lepas dari masalah kecemasan. Kecemasan merupakan perasaan yang tidak menyenangkan dan dapat menimbulkan gejala fisiologis, emosionalitas dan kognitif yang dapat menghambat performa terbaik dari seseorang. Tujuan penelitian ini untuk mengetahui perbedaan tingkat kecemasan Mahasiswa jenjang Sarjana dan Magister menjelang Ujian Akhir Semester. Partisipan penelitian adalah mahasiswa jenjang sarjana dan magister sejumlah 35 orang dengan non-probability purposive sampling dan quota sampling. Instrumen pengukuran kecemasan yang digunakan adalah skala kecemasan dalam menghadapi ujian akhir semester. Teknik analisis menggunakan independent t-test. Hasil penelitian ini menunjukkan Skor p > 0.05 artinya tidak ada perbedaan signifikan dalam tingkat kecemasan antara mahasiswa sarjana dan magister menjelang Ujian Akhir Semester. Implikasinya, tingkat kecemasan tidak tergantung pada jenjang pendidikan. Saran untuk penelitian selanjutnya adalah dapat mempertimbangkan faktor-faktor lain untuk mendapatkan pemahaman yang lebih komprehensif dan berkontribusi pada tingkat kecemasan pada mahasiswa sarjana dan magister menjelang ujian serta intervensi apa yang dapat dilakukan untuk membantu mengurangi kecemasan mahasiswa jenjang sarjana maupun magister selama masa ujian akhir semester.